(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The article is aiming to prove the necessity and prospects for developing the new Kazakhstanian research fieldinvestigation of the Kazakh title nation language consciousness; the paper determines the objective area of such investigations in the Kazakhstan Ethnic Psycho Linguistics and Lingua Culture Study, formulates their aims and targets, and discusses the problems of revealing the most meaningful (mentally marked) concepts of the Kazakh culture, operating the method of the free associative experiment. In the content of the article reflected the stages of the work on the free associative experiment is a list of wordsincentives in the questionnaire, the methodology of the analysis of the received material, marked by features of perception and associative response informants, characterizing the national-cultural specificity of the linguistic consciousness of modern Kazakhs. Taken by the author of the study allows to draw conclusions on the effectiveness and prospects of the use of associative methodologies in the study of the linguistic consciousness, in the definition of ethno-cultural conceptual sphere of the Kazakh nation and to identify its priority values.